2016
DOI: 10.1371/journal.pone.0167241
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low-Calorie Sweetener Use and Risk of Abdominal Obesity among Older Adults: A Cohort Study

Abstract: IntroductionLow-calorie sweetener use for weight control has come under increasing scrutiny as obesity, especially abdominal obesity, remain entrenched despite substantial low-calorie sweetener use. We evaluated whether chronic low-calorie sweetener use is a risk factor for abdominal obesity.Participants and MethodsWe used 8268 anthropometric measurements and 3096 food diary records with detailed information on low-calorie sweetener consumption in all food products, from 1454 participants (741 men, 713 women) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 48 publications
(55 reference statements)
1
27
0
1
Order By: Relevance
“…Animal studies have shown weight gain and metabolic dysregulation after intake of NNS [ 29 , 30 ]. NNS are not inert substances, and physiological effects on metabolism and energy balance have been proposed to explain an unexpected weight-inducing effect in long-term follow-up studies in children and adults [ 7 , 31 33 ]. NNS affect the glucose metabolism and have been associated with type 2 diabetes [ 24 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown weight gain and metabolic dysregulation after intake of NNS [ 29 , 30 ]. NNS are not inert substances, and physiological effects on metabolism and energy balance have been proposed to explain an unexpected weight-inducing effect in long-term follow-up studies in children and adults [ 7 , 31 33 ]. NNS affect the glucose metabolism and have been associated with type 2 diabetes [ 24 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been an increase in the overweight and obese population. In the US, body mass index (BMI), an important index to evaluate tissue mass, has recently increased to 35 % for men and 40 % for women (Chia et al, 2016). Approximately two thirds of American adults are considered overweight, whereas one third are classified as obese (Smith et al, 2016).…”
Section: Sweeteners Obesity and Diabetesmentioning
confidence: 99%
“…High-potency sweeteners (HPS), which bind and activate T1Rs to stimulate sweet taste, present a low-or no-calorie alternative to sugar consumption. Although some observational studies have shown that "diet" beverage consumption is not associated with weight loss [34,35] , several clinical studies have found that they can be effective tools for achieving weight loss [36,37] . As will be discussed below, the recent discovery of taste receptors in metabolically active tissues has generated intense interest in the potential health impacts of HPS.…”
Section: T1rs Guide Food Selectionmentioning
confidence: 99%